A real-life experience with eculizumab and efgartigimod in generalized myasthenia gravis patients - Pane, Chiara; Di Stefano, Vincenzo; Cuomo, Nunzia; Sarnataro, Alessio; Vinciguerra, Claudia; Bevilacqua, Liliana; Brighina, Filippo; Rini, Nicasio; Puorro, Giorgia; Marsili, Angela; Garibaldi, Matteo; Fionda, Laura; et al. (Journal of neurology, 2024)
Introduction Eculizumab, a complement active antibody, and efgartigimod, an Fc fragment that blocks neonatal Fc receptor, are both approved to treat generalized myasthenia gravis (gMG) patients. The objective of this study is to describe the clinical response to both treatments in a real-life setting. Methods We collected baseline and follow-up clinical data using the Myasthenia Gravis-Activities of Daily Living (MG-ADL), and Quantitative Myasthenia Gravis (QMG). We included 63 patients, 32 treated with eculizumab and 31 with efgartigimod. Of the efgartigimod-treated patients, 22 were anti-acetylcholine receptor antibody-positive (AChR-Ab +) and 9 were AChR-Ab- (3 MuSK-Ab + and 6 seronegative). Results Both treatments showed similar efficacy relative to the MG-ADL scale reduction ( p = 0.237). Efgartigimod had a similar effect on both AChR-Ab + and AChR-Ab- ( p = 0.280). Eculizumab was superior to efgartigimod relative to the QMG score reduction for the entire dataset ( p = 0.003) and was more likely to achieve a clinical response at the QMG compared to efgartigimod (OR 1.373; p = 0.016). Steroid-sparing effect was higher for eculizumab than efgartigimod ( – 16.7 vs  – 5.2 mg of the baseline daily dose at follow-up; p = 0.001). Mean speed of prednisone reduction was  – 13.1 mg of the daily dose for each month of follow-up for eculizumab-treated patients and  – 3.2 for efgartigimod ( p = 0.001). We found three serious events, all not related to treatment in the investigator’s opinion. One eculizumab-treated patient experienced a severe pneumonia and died despite treatment. Conclusions Our study provides evidence that eculizumab and efgartigimod can be used in clinical practice to reduce disability in gMG patients. Eculizumab-treated patients had a higher QMG response and steroid sparing effect. Efgartigimod may offer a more flexible schedule due to its cyclical use, no need for vaccination, and efficacy in AChR-Ab- patients.